What Explains the Wealth Gap Between Immigrants and the New Zealand Born? - John Gibson; Trinh Le; Steven Stillman (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
Immigrants are typically found to have less wealth and hold it in different forms than the native born. These differences may affect both the economic assimilation of immigrants and overall portfolio allocation when immigrants are a large share of the population, as in New Zealand. In this paper, data from the 2001 Household Savings Survey are used to examine wealth differences between immigrants and the New Zealand-born. Differences in the allocation of portfolios between housing and other forms of wealth are described. Unconditional and conditional wealth quantiles are examined using parametric models. Semiparametric methods are used to decompose differences in net worth at different parts of the wealth distribution into the part due to differences in characteristics and the part due to differences in the returns to characteristics.
Keywords: D31; G11; J15; 330